RENDAHNYA HASIL BELAJAR SISWA TERHADAP MATA PELAJARAN MATEMATIKA SISWA KELAS XI DI SMK NEGERI 1 GUGUK TAHUN 2022/2023 - Wini Sri Afriani; Isnaniah Isnaniah; Emrani Damir (KOLONI, 2022)
This study discusses the low mathematics learning outcomes of student at SMK Negeri 1 GUGUK in class XI Multimedia. The purpose of this study is to find out the low mathematics learning outcomes of student in class XI Multimedia. The sample used consisted of 29 student with 13 female students and 16 male students. The research data collection used the result of observations and interviews with the mathematics teacher in class XI, while the results of the research were that the dayli test result in class XI Multimedia were very low and the majority were below the KKM (Minimum Completeness Criteria), only 10 out of 29 students who were above KKM is around 34.48% and below the KKM is 65.51%. Keywords: Learning outcomes, Mathematics